2008
DOI: 10.1007/s12149-007-0179-8
|View full text |Cite
|
Sign up to set email alerts
|

Maximal safe dose of I-131 after failure of standard fixed dose therapy in patients with differentiated thyroid carcinoma

Abstract: The maximal safe dose provides an effective means of treatment in patients who failed to respond adequately to conventional fixed dose therapy. I-131 MSD therapy can be considered in patients who fail fixed dose therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…This approach was implemented more than 50 years ago by Benua et al [1], and was successfully applied in the following decades by Leeper [2]. Unfortunately, the method has now been abandoned by many institutions, but it has continued in use in other centres [3][4][5][6][7][8]. The method provides solid indications of best outcome, in contrast to the fixed activity approach [3,4], although a clinical study with the highest level of evidence (phase III randomized) has never been pursued.…”
Section: Formalization Of the Optimization Principle In The New Europmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach was implemented more than 50 years ago by Benua et al [1], and was successfully applied in the following decades by Leeper [2]. Unfortunately, the method has now been abandoned by many institutions, but it has continued in use in other centres [3][4][5][6][7][8]. The method provides solid indications of best outcome, in contrast to the fixed activity approach [3,4], although a clinical study with the highest level of evidence (phase III randomized) has never been pursued.…”
Section: Formalization Of the Optimization Principle In The New Europmentioning
confidence: 99%
“…Unfortunately, the method has now been abandoned by many institutions, but it has continued in use in other centres [3][4][5][6][7][8]. The method provides solid indications of best outcome, in contrast to the fixed activity approach [3,4], although a clinical study with the highest level of evidence (phase III randomized) has never been pursued. This approach was recently re-proposed [9], with the introduction of the acronym AHASA (as high as safely attainable) instead of ALARA.…”
Section: Formalization Of the Optimization Principle In The New Europmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also note that such treatment almost always produced a partial biochemical tumor response. Lee et al (2008) likewise determined the maximal safe activity calculated according to the original Benua approach for 47 patients. Their mean calculated safe activity was 12.5 GBq.…”
Section: Optimized Treatment Using High Activitiesmentioning
confidence: 99%
“…While we consider that the study by Klubo-Gwiezdzinska provides an initial indication in favour of AHASA, Lee et al found that 45% of patients who failed to respond to pretreatment with a fixed activity approach, achieved a partial or complete radiological response after ASAHA therapy [22]. Though at a low level of evidence, it nonetheless seems that there are at least two papers supporting the advantages of AHASA.…”
mentioning
confidence: 86%